Influence of Varied Fluorine Contents on Long-Term Storage Stability of Polyacrylate Nanoparticles and Film Properties. (31st October 2019) - Liu, Hongzhu; Zhang, Gaofan; Lu, Lulu; Chen, Yuexing; Luo, Mengting; Bian, Jiming; Wang, Zefeng; Wang, Lijin
Abstract : Polyacrylate nanoparticles are widely applied and typically prepared by many polymerization methods. However, poor long-term storage stability of nanoparticles limited their use, so some methods are carried out to overcome it. In this paper, we investigated a series of fluorinated polyacrylate nanoparticles to improve the long-term storage stability of polyacrylate nanoparticles. We found that increasing fluorine content resists the aggregation of nanoparticles during long-term storage. Furthermore, a higher content of fluorine can improve the hydrophobicity of latex polyacrylate film and increase the refractive index of latex polyacrylate film. The properties of the polyacrylate nanoparticles and latex film can thus be controlled by changing fluorine contents, which in turn provides key insights into the design of functional polymer material.